Karakteristik Manajemen Pendidikan Profetik - Rima Umaimah (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2021)
The purpose of this study is to understand and determine the characteristics of Islamic education management. The method used by the writer in this research is literature, through primary data reading primary books. This study involved colleagues, namely Islamic education lecturers from various campuses with the following steps: testing the manuscript through discussion, criticism, suggestions, improvement, and finalization. Based on the results of the study it can be concluded: The characteristics of Islamic education management are holistic, meaning that the management strategy of Islamic education management is carried out by combining learning resources and taking into account the involvement of human culture, both political, economic, intellectual and theological.